Stiffness Model and Experimental Study of Hydrostatic Spindle System considering Rotor Swing - Runlin Chen; Xingzhao Wang; Chen Du; Jun Zha; Kai Liu; Xiaoyang Yuan (Shock and Vibration)
For high-end CNC machine tools, the stiffness of the spindle system is one of the most important performance indicators. In this paper, the hydrostatic motorized spindle system of a grinding machine is taken as the research object, and a two-degree-of-freedom stiffness model of the spindle system considering rotor swing is proposed. The stiffness of the spindle system under different excitation frequencies is analyzed, and the contributions of the stiffness of two bearings to the stiffness of the spindle system are evaluated. The vibration test on the spindle system is implemented through the hammering method. The vibration responses of the spindle system are obtained, and the stiffness of the spindle system is identified. The results show that the test results of the stiffness of the spindle system are in good agreement with the theoretical calculation, with an average error of about 14.21%. The research in this paper can provide theoretical and data support for bearing design and stiffness evaluation of a hydrostatic spindle system.